LANDASAN TEOLOGI PRAKTIK RITUAL HINDU - Widana, I Gusti Ketut; Suasthi, I Gusti Ayu (WIDYANATYA, 2019)
Basically, ritual activities are a series of sacred (sacred / sacred) actions carried out by Hindus using certain tools, places, and certain ways. Its main function is as a medium to surrender by worshiping God along with His manifestations accompanied by various offerings while accompanied by prayers (mantras) in order to obtain a gift of salvation. The rituals that are often encountered and experienced and carried out in daily life are generally life cycle rituals such as the rituals of birth, marriage, until death that are religiously believed by followers. Hinduism itself as a religion constructed by three basic frameworks positions "ritual" (event) as a supplement of material (skin / packaging) to support the element of "ethics" (moral) as part of an essence that is strengthened as well as to strengthen the foundation of "philosophy" (tattwa) as substance.